Effectiveness of an information booklet on Prevention and early detection of cervical cancer in terms of knowledge among female school teachers in selected secondary schools in Mairang Town, Meghalaya State - Khumukcham Anupama Devi; Ibandalyne Nongsiej (International Journal of Medical Research and Review, 2023)
Introduction: A pre-experimental study was undertaken with one group pretest posttest design to find the effectiveness of Information booklet on knowledge of female school teachers regarding prevention and early detection of cervical cancer in selected secondary schools, Mairang Town, Meghalaya State. Objectives: The main objectives of the study were to assess the knowledge of female school teachers on prevention and early detection of cervical cancer before and after administering the information booklet and to evaluate the effectiveness of information booklet on prevention and early detection of cervical cancer in terms of gain in knowledge. Material and Methods: The conceptual frame work adopted for the study was based on Health Belief Model. The sample size is 30, non-probability purposive sampling is the sampling technique adopted. The data was collected by using the structured knowledge questionnaire. Result: The findings of the study revealed that the mean posttest knowledge scores (23.17) of the teachers was higher than the pretest knowledge scores (12.83). The obtained mean difference was found to be statistically significant at 0.05 level of significance, as evident from calculated ‘t’(29)= 20.09, there by indicating the effectiveness of the information booklet regarding prevention and early detection of cervical cancer. Conclusion : The information Booklet on prevention and early detection of cervical cancer was effective for increasing the knowledge